Phases of the summer monsoon equatorial trough and oscillations of the equatorial trough - PANT, P. S. (MAUSAM, 1980)
In continuation of earlier studies by Pant (1978), the, oscillations of the equatorial trough and the associated phases of the summer monsoon over the Indian subcontinent were studied. For this purpose, the data relating to MONEX-79 were also considered. A "weak" or "break" monsoon phase is associated with the insitu appearance of the planetary oceanic equatorial trough in the lower troposphere around 10 deg. N. The revival of the monsoon activity is associated with the northward progress of the southern trough and its re-establishment around 20 deg. N. Study of mid-tropospheric temperature, changes over Tibet and Sinkiang have brought out clearly that the setting in of "weak" or "break" 'monsoon condition is concurrent with the occurrence of very low temperatures in the middle troposphere, particularly over Sinkiang. The physical picture that emerges from this study is that under low zonal index conditions advection of cold air behind large amplitude middle latitude troughs results in cooling of the Tibetan Plateau and the neighbourhood in the middle levels. This results in the destruction of the reverse Hadley cell and re-establishment of the direct cell with its upward limb near 10-15 deg. N. This is a physically consistent picture and explains many of the observed characteristics of the weak and active phases of the monsoon described by several authors. The results of the study hold out possibilities of prediction of the phases of the monsoon over periods of a week to ten days based on the temperature changes over the Asian continent to the north of India.